Experiment and modeling of low-concentration methane catalytic combustion in a fluidized bed reactor. (25th January 2016) - Yang, Zhongqing; Yang, Peng; Zhang, Li; Guo, Mingnv; Ran, Jingyu
Highlights: The catalytic combustion of 0.15 3 vol. % low concentration methane in a fluidized bed was studied. A mathematical model was proposed on the basis of gas–solid flow theory. A comparative analysis of the established model with plug flow, mixed flow and K-L models was carried out. The axial methane profile along fluidized bed was predicted by using the mathematical model. The bed temperature has greater impact on methane conversion than fluidized velocity. Abstract: This study undertakes a theoretical analysis and an experimental investigation into the characteristics of low-concentration methane catalytic combustion in a bubbling fluidized bed reactor using 0.5 wt.% Pd/Al2 O3 as catalytic particles. A mathematical model is established based on gas–solid flow theory and is used to study the effects of bed temperature and fluidized velocity on methane catalytic combustion, and predict the dimensionless methane concentration axial profile in reactor. It is shown that methane conversion increases with bed temperature, but decreases with increasing fluidized velocity. These theoretical results are found to correlate well with the experimental measurement, with a deviation within 5%. A comparative analysis of the developed model with plug flow, mixed flow and K-L models is also carried out, and this further verifies that the established model better reflects the characteristics of low-concentration methane catalytic combustion in a bubbling fluidized bed. Using this reaction model, it was found that the difference in methane conversion between dense and freeboard zones gradually increases with bed temperature; the dense zone reaction levels off at 650 °C, thereby minimizing the difference between the dense and freeboard regions to around 15%. With an increase in bed temperature, the dimensionless methane concentration in the dense zone decreases exponentially, while in the splash zone, it varies from an exponential decay to a slow decrease. In contrast, there is very little change in the homogeneous zone, meaning that combustion mainly occurs in the dense zone and moves toward the lower part of the bed with increasing bed temperature.